Investigation of the visual appearance of different skirt styles and materials during the fitting simulation with Lectra Modaris - Tibifez Hailu Nechno; Yordan Kyosev; Mulat Alubel; Sybille Krzywinski (Communications in Development and Assembling of Textile Products)
This paper examines the influence of different fabric types and material properties on the visual appearance of three types of skirt styles using numerical simulation. The purpose of the simulation is to present and analyze the appearance of virtual garments, create the best-fitting pattern pieces, and choose the appropriate fabric type based on the multiple clothing styles to achieve the intended design. The results show that when the type of fabric changes without changing the clothing style and on the other hand the style changes without changing the type of material, the appearance of the garment changes and the effect can be clearly seen with the 3d comparison result. These changes should be taken into account when choosing the right fabric for different styles.